The puzzling influence of Ophiomorpha (trace fossil) on reservoir porosity: X-ray microtomography analysis - Miguez-Salas, Olmo; Cabrera Ortiz, Jose; Dorador, Javier; Rodríguez-Tovar, Francisco J. (Frontiers in Earth Science, 2022)
Bioturbation can influence petrophysical properties (e.g., porosity, permeability) of sedimentary rocks and, in consequence, reservoir quality. The impact can be positive, negative, or neutral, requiring detailed ichnological analysis. Ophiomorpha, a branched cylindrical burrow with diagnostic peloidal wall, may be present in bioturbated reservoirs that exhibit properties of both super-permeability and reduced porosity/permeability. However, a mechanistic understanding of how Ophiomorpha positively or negatively impacts petrophysical properties has not yet been established. This study presents high-resolution X-ray microtomographic analysis of how the features of Ophiomorpha (i.e., peloidal wall vs. burrow fill) influence porosity distribution in deep-water deposits (Neogene Tabernas Basin, SE Spain). The results show that the peloidal burrow wall exhibits the lowest porosity (up to six orders of magnitude lower than burrow fill or host sediment), while surrounding sediment shows variable values. Abrupt porosity changes within the fill material likely relate to burrow-associated diagenesis. A refined understanding of the features of Ophiomorpha and their associated porosity distribution help to constrain understanding of their diverse impacts on reservoir properties.